Enhancing Resilience through Emotional Intelligence in Religious Communities for Crime Prevention Post-COVID-19 - Lemon Madoda Phiri; Adewale A. Olutola; Jacob Tseko Mofokeng (Khazanah Theologia, 2023)
The aftermath of COVID-19 has wrought significant emotional distress, exacerbating the incidence of emotionally motivated crimes, particularly within families. This phenomenon presents a substantial challenge to the South African Police Service (SAPS), especially due to the private nature of these crimes. In response, this study investigates whether the religious community in the Mamelodi policing area can leverage emotional intelligence (EI) to foster resilience and aid in crime prevention. We employed a quantitative approach, utilizing non-probability sampling to survey 104 adult Christians in Mamelodi. Participants provided informed consent. The Trait Emotional Intelligence Questionnaire-Short Form (TEIQue-SF) was used for assessment, covering four EI variables: emotionality, self-control, sociability, and well-being. The findings reveal a high level of EI, with scores of 74.06% for emotionality, 68.41% for self-control, 59.26% for sociability, and an impressive 86.84% for well-being, culminating in an overall EI score of 72.14%. These results suggest that Mamelodi's churches are effective community-based entities capable of collaborating with SAPS to prevent emotionally driven crimes, through resilience-building rooted in EI competencies. This research contributes to the South African academic discourse by intersecting psychology, policing, and community studies, particularly focusing on a township population often living below the poverty line and with limited EI awareness.